Halal Industry and Science: Analysis of Epistemological Reasoning of Halal Center Institution UNEJ and Halal Assurance Institution UIN KHAS Jember Integration Interconnection Perspective - Syafiqi, Ahmad Tamam; Nazar, Muhnazar Arifin; Al-Asy'ari, M. Khoirul Hadi (Kaunia: Integration and Interconnection Islam and Science Journal, 2024)
The halal industry has experienced significant growth, thus requiring a deeper understanding of the epistemological foundation of halal institutions, especially in Universitas Jember (UNEJ) and Universitas Islam Negeri Kiai Haji Achmad Siddiq (UIN KHAS) Jember. This analysis explores the integration and interconnection of halal science and its institutions, emphasizing the importance of the tawidik paradigm in halal research and practice. The halal certification process, influenced by environmental pressures and institutional theory, highlights the need for effective management and adherence to Islamic principles in halal assurance practices. Furthermore, the philosophy of halal science, rooted in the Qur'an, underlines the need to align halal practices with Islamic values, ensuring that innovations in the halal sector do not compromise religiously bound principles. By examining the role of these institutions, this study aims to propose a framework for enhancing scientifically sound and spiritually aligned halal assurance, encouraging a holistic approach to halal industry development. There are two key questions in this study. First, what is the concept of halal industry and science in Indonesia? Second, how is the Analysis of Epistemological Reasoning of the Halal Center Institution of UNEJ and the Halal Assurance Institution of UIN Khas Jember from the Integration Interconnection Perspective? Using a qualitative research approach and observation, interview, and documentation methods to discuss the Epistemological Reasoning Analysis of the Halal Center Institution of UNEJ and the Halal Assurance Institution of UIN Khas Jember from the Integration Interconnection Perspective and the content analysis approach to explain the study of the concept of halal industry and science in Indonesia. So the results of this study are to find out the concept of halal industry and science in Indonesia and the second is the Epistemological Reasoning Analysis of the UNEJ Halal Center Institution of UNEJ and the Halal Assurance Institution of UIN Khas Jember from the Integration Interconnection Perspective.